Efficient energy management measures in steel industry for economic utilization - Gurinderbir Singh Grewal; Bharat Singh Rajpurohit (Energy Reports, 2016)
The application of energy efficient Induction Machines (IM) is explained in reference to power consumption savings. In energy efficient IM, losses for various Horse Power (HP) ratings are summarized for bringing effective changes in design. Emphasis is laid on how load factor, speed & power quality affect machine's efficiency. Replacement of conventional IM of higher power rating is done with required energy efficient Doubly Fed Induction Machine (DFIM) to enhance the performance at variable speeds near rated power outputs. Results of the proposed approach will give substantial savings in energy & loss reduction. The field data of Jindal Steel Rolling Mill (JSRM) at Hisar, Haryana (India) is taken into consideration. This paper proposes a non-intrusive air gap torque method for efficiency estimation of in-service IMs. This approach gives results considering stray-load and friction-windage loss according to IEC standard and IEEE112-B standard. The proposed method is validated experimentally whose effectiveness is witnessed using MATLAB/SIMULINK.
Keywords: 330; Air-gap torque; Efficiency estimation; Induction machine (IM); Steel rolling mill; Techno-economics; Unbalancing in voltage